New Insights Into the Biology of Protein O-GlcNAcylation: Approaches and Observations - Mueller, Toni; Ouyang, Xiaosen; Johnson, Michelle S.; Qian, Wei-Jun; Chatham, John C.; Darley-Usmar, Victor; Zhang, Jianhua (Frontiers in Aging, 2021)
O-GlcNAcylation is a protein post-translational modification that results in the addition of O-GlcNAc to Ser/Thr residues. Since its discovery in the 1980s, it has been shown to play an important role in a broad range of cellular functions by modifying nuclear, cytosolic, and mitochondrial proteins. The addition of O-GlcNAc is catalyzed by O-GlcNAc transferase (OGT) and its removal is catalyzed by O-GlcNAcase (OGA). Levels of protein O-GlcNAcylation change in response to nutrient availability and metabolic, oxidative, and proteotoxic stress. OGT and OGA levels, activity, and target engagement are also regulated. Together this results in adaptive and, on occasion, detrimental responses that affect cellular function and survival, which impact a broad range of pathologies and aging. Over the past several decades, approaches and tools to aid the investigation of the regulation and consequences of protein O-GlcNAcylation have been developed and enhanced. This review is divided into two sections: 1) We will first focus on current standard and advanced technical approaches for assessing enzymatic activities of OGT and OGT, assessing the global and specific protein O-GlcNAcylation, and 2) We will summarize in vivo findings of functional consequences of changing protein O-GlcNAcylation, using genetic and pharmacological approaches.